محمد ناصر في عيون بعض العارفين الآسيويين Mohammad Natsir in the eyes of prominent Asian leaders - Solihin, Sohirin Mohammad; Nasser, Youcef (International Islamic University Malaysia, 2019)
يستعرض هذا البحث مكانة محمد ناصر الوزير والمفكِّر والداعية والمصلح في بلاده إندونيسيا بخاصة وآسيا بعامة. كما يبسط رأي الشخصيات الآسيوية في شخص محمد الناصر لا سيما من الذين عايشوه من قرب واحتكوا به وأفادوا منه، أمثال: أمين رئيس، وأنور إبراهيم، وفوكودا، وغيرهم من العارفين الآسيويين الذي تقلَّدوا مناصب عليا في بلادهم وأسمعوا صوتهم للعالم؛ إذ أجمعوا على أن محمد ناصر أرض هادرة، وعملة نادرة ليست قابلة للسكِّ، وحكاية غير عابرة بل حاضرة في وجدان كل إنسان في قلبه إنسان. The paper attempts to expose the position of Muhammad Natsir in his capacity as Prime Minister, thinker, preacher and Muslim reformer of Indonesia and Asia in general. Prominent figures, such as Amin Rais, Dato Seri Anwar Ibraham and Takeo Fukuda and many others who occupied high post within the government gave high appreciation on personal characters of Mohammad Natsir. He is beyond any doubt possessed valuable character and left lasting memory in human history.